Betacellulin-induced beta cell proliferation and regeneration is mediated by activation of ErbB-1 and ErbB-2 receptors. - Yoon Sin Oh; Seungjin Shin; Youn-Jung Lee; Eung Hwi Kim; Hee-Sook Jun (PLoS ONE, 2011)
Background Betacellulin (BTC), a member of the epidermal growth factor family, is known to play an important role in regulating growth and differentiation of pancreatic beta cells. Growth-promoting actions of BTC are mediated by epidermal growth factor receptors (ErbBs), namely ErbB-1, ErbB-2, ErbB-3 and ErbB-4; however, the exact mechanism for beta cell proliferation has not been elucidated. Therefore, we investigated which ErbBs are involved and some molecular mechanisms by which BTC regulates beta cell proliferation. Methodology/principal findings The expression of ErbB-1, ErbB-2, ErbB-3, and ErbB-4 mRNA was detected by RT-PCR in both a beta cell line (MIN-6 cells) and C57BL/6 mouse islets. Immunoprecipitation and western blotting analysis showed that BTC treatment of MIN-6 cells induced phosphorylation of only ErbB-1 and ErbB-2 among the four EGF receptors. BTC treatment resulted in DNA synthetic activity, cell cycle progression, and bromodeoxyuridine (BrdU)-positive staining. The proliferative effect was blocked by treatment with AG1478 or AG825, specific tyrosine kinase inhibitors of ErbB-1 and ErbB-2, respectively. BTC treatment increased mRNA and protein levels of insulin receptor substrate-2 (IRS-2), and this was blocked by the ErbB-1 and ErbB-2 inhibitors. Inhibition of IRS-2 by siRNA blocked cell cycle progression induced by BTC treatment. Streptozotocin-induced diabetic mice injected with a recombinant adenovirus expressing BTC and treated with AG1478 or AG825 showed reduced islet size, reduced numbers of BrdU-positive cells in the islets, and did not attain BTC-mediated remission of diabetes. Conclusions/significance These results suggest that BTC exerts proliferative activity on beta cells through the activation of ErbB-1 and ErbB-2 receptors, which may increase IRS-2 expression, contributing to the regeneration of beta cells.